2009
DOI: 10.1007/s00432-009-0708-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and protein changes of E-cadherin in meningiomas

Abstract: Our results suggest that genetic instabilities of the E-cadherin gene have a role in meningioma development and progression. Detected microsatellite instability indicates that mismatch repair may also be targeted in meningioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 27 publications
0
26
1
Order By: Relevance
“…SFRP3, another Wnt pathway antagonist, reduces activity of metalloproteinases and activation of β-catenin and thus inhibits epithelial-mesenchymal transition (EMT) seen in several cancer types [22,23]. We observed statistically significant decreased of the amount of SFRP3 protein expression in our total renal cancer clear cell tumors compared with normal kidney tissues.…”
Section: Discussionmentioning
confidence: 56%
“…SFRP3, another Wnt pathway antagonist, reduces activity of metalloproteinases and activation of β-catenin and thus inhibits epithelial-mesenchymal transition (EMT) seen in several cancer types [22,23]. We observed statistically significant decreased of the amount of SFRP3 protein expression in our total renal cancer clear cell tumors compared with normal kidney tissues.…”
Section: Discussionmentioning
confidence: 56%
“…In esophageal squamous cell carcinoma (ESCC), overexpression of FRAT1 is associated with increased cell proliferation and aberrant activation of the β-catenin/TCF pathway, a consequence of nuclear accumulation of β-catenin that promotes the transcriptional activity of β-catenin/TCF [34]. Interestingly, also higher-grade meningiomas exhibit increased protein level and nuclear/perinuclear localization of β-catenin [31, 35], suggesting aberrant activation of the Wnt signaling pathway [9]. In gliomas, overexpression of FRAT1 is correlated with a malignant phenotype, higher cell proliferation, decreased apoptosis and poor prognosis [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…This observation is consistent with our result that downregulation of miR-34a-3p reduced apoptosis of meningioma cells in vitro . The exhibited nuclear accumulation of β-catenin in higher-grade meningiomas [31, 35] may be, in part, due to loss of translational repression of FRAT1 due to the decreased levels of miR-34a-3p.…”
Section: Discussionmentioning
confidence: 99%
“…Since beta-catenin is an integral part of the C-terminal intracellular complex of E-cadherin therefore E-cadherin is indirectly involved in the relevant cancerrelated pathophysiology [36]. A recent study using 60 meningioma tissues revealed sporadic E-cadherin expression in the tumors that further strengthen our understanding of the role of E-cadherin in meningiomas [37].…”
Section: E-cadherin In Nerve-tissue Cancermentioning
confidence: 90%